PERSPEKTIF GURU TERHADAP FAKTOR INTERNAL DAN EKSTERNAL DISPILIN SISWA DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Perlindungan Waruwu, Agusmen; lyesmaya, Dyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research analyzes the effect of internal and external factors on student discipline in Pancasila and Civic Education (PPKn) at the elementary school level, providing a comparative spatial mapping between West Java and West Nias. Applying a quantitative causal-comparative design, this study involved a saturated sample of 30 elementary school teachers. Data collection utilized a closed questionnaire with 18 Likert-scale items, validated and declared reliable (Variables X1=0.697, X2=0.759, Y=0.785). Data were analyzed using Multiple Linear Regression. The findings reveal that partially, internal factors (student self-awareness) and external factors (teacher modeling and school climate) significantly and positively affect student discipline. Spatially, student discipline in both West Java (M=3.36) and West Nias (M=3.18) falls into the "Good" category, with external environment emerging as the most dominant aspect influencing compliance. These results underscore that integrating internal moral development and structured external reinforcement is imperative for optimizing student discipline.